Sociodemographic, Psychological, and Lifestyle Characteristics Are Associated with a Liking for Salty and Sweet Tastes in French Adults. Issue 3 (28th January 2015) - Lampuré, Aurélie; Schlich, Pascal; Deglaire, Amélie; Castetbon, Katia; Péneau, Sandrine; Hercberg, Serge; Méjean, Caroline
Abstract: Background: Various studies have shown that sensory liking influences dietary behavior and that individual characteristics are related to food intake and weight status, but little is known about individual profiles associated with salt and sweet liking. Objective: The aim of the present study was to investigate the association between a liking for salty and sweet tastes (i.e., a liking for foods rich in salt or sugar and preferred amounts of salt or sugar seasoning in foods) and sociodemographic, psychological, and lifestyle characteristics in a large sample. Methods: Individual factors and liking scores were collected by validated questionnaires from 37, 181 French adults participating in the NutriNet-Santé study, a large web-based observational cohort launched in 2009 that studies relations between nutrition and health. The associations were assessed by multivariable multinomial logistic regression models adjusted for socioeconomic, anthropometric, and health variables. Results: In both genders, with increasing age, individuals were more likely to have a high salt liking (men, OR: 1.24; 95% CI: 1.18, 1.30; women, OR: 1.14, 95% CI: 1.09, 1.19), whereas they were less likely to have a strong sweet liking (men, OR: 0.87; 95% CI: 0.83, 0.91; women, OR: 0.66; 95% CI: 0.64, 0.68). Current smokers (men, OR: 2.30; 95% CI: 1.90, 2.78; women, OR: 1.50; 95% CI: 1.36, 1.66) and heavy drinkers (men, OR: 2.92; 95% CI: 2.37, 3.58; women, OR: 2.57, 95% CI: 2.22, 2.98) were more likely to like salt than nonsmokers and alcohol abstainers. Regarding the sweet taste, women smokers were less likely to like sweets (OR: 0.80; 95% CI: 0.72, 0.89). Highly uncontrolled eaters [men, OR: 2.39; 95% CI: 2.04, 2.80; women, OR: 2.22; 95% CI: 1.99, 2.47) and highly emotional women (OR: 1.35; 95% CI: 1.18, 1.55) were more likely to have a high liking for sweets than slightly uncontrolled eaters and nonemotional eaters, whereas those with high cognitive restraint (men, OR: 0.39; 95% CI: 0.33, 0.46; women, OR: 0.55; 95% CI: 0.50, 0.60) and former weight-loss dieters (men, OR: 0.60; 95% CI: 0.52, 0.70; women, OR: 0.68; 95% CI: 0.62, 0.73) were less likely to have a strong sweet liking compared with those with low cognitive restraint and never-dieters. Conclusion: An unhealthy lifestyle that includes smoking and alcohol consumption may influence salt liking, and eating behavior may have an impact on sweet liking. Further research is needed to study the influence of individual factors and sensory liking on dietary intake and weight status. This study was registered at the European Clinical Trials Database as 2013–000929–31.